2013
DOI: 10.1021/jf403276y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Infrared and Raman Spectroscopies for Identification of Juvenile Black Seabream (Sparus macrocephalus) Intoxicated by Heavy Metals

Abstract: The potential application of infrared and Raman spectroscopies was explored as rapid and nondestructive tools for the identification of juvenile black seabream samples intoxicated by heavy metals (Zn, Cu, and Cd). Discrimination models were established on the basis of the infrared and Raman spectral data using three calibration methods, namely, partial least-squares discriminant analysis, least-squares support vector machines, and random forest. The combination of two spectroscopies was studied, in which three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Therefore, those important variables can be selected according to the V value. The expression of V is shown in following formula (1).…”
Section: Pls-vip and Pls-uve Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, those important variables can be selected according to the V value. The expression of V is shown in following formula (1).…”
Section: Pls-vip and Pls-uve Modelsmentioning
confidence: 99%
“…Multivariate calibration models have been widely applied in analytical chemistry, especially in the field of spectroscopy analysis . However, when full wavelengths are considered as input variables, many uninformative and noise variables may interfere with the input, which results in a reduction in the accuracy and robustness of a prediction model .…”
Section: Introductionmentioning
confidence: 99%
“…As the relationship between the spectra of the tested sample and its quality may have linear or non-linear characteristics or both of them, two typical calibration methods of partial least square regression (PLSR) and least-squares support vector machines (LS-SVM) were considered and compared, in which the former one is a classical linear regression method, while the latter is commonly used to establish non-linear calibration models. PLSR has been widely employed for spectral quantitative prediction (Chen et al 2013;Huang et al 2014;Wu et al 2014b). In the PLSR calibration, the response variable is taken into account in the process of extracting the latent variables, which is an important advantage of PLSR against principal component regression.…”
Section: Spectral Preprocessing and Model Calibrationmentioning
confidence: 99%
“…[7][8][9] It has been demonstrated that these spectroscopic methods can be intensively used to make a reasonable comprehensive evaluation of fish, chicken, beef, and pork. [10][11][12] In particular, hyperspectral imaging technique, as an emerging and promising tool, has gained importance in the inspection of meat quality and safety. 13,14 Considerable research has been reported on this novel optical measurement to assess quality and safety of meat, which generally encompass nutritional components analysis (moisture, fat, protein), 15 edible quality evaluation (color, marbling, tenderness), 16 technological attributes determination (water-holding capacity, pH) 17 as well as microbiological spoilage assessment.…”
Section: Introductionmentioning
confidence: 99%